EFFECT OF NITROGEN AND PHOSPHORUS LEVELS ON YIELD POTENTIAL OF OAT-BERSEEM FORAGE GROWN WITH DIFFERENT SEED PRODUCTION IN SEMI ARID TRACT OF HARYANA - Tomer, P S; Arora, N D (Annals of Arid Zone, 2016)
Growing of 1/2 berseem + 1/2 oat mixture proved to be the bestby yielding 95.2, 6.0, 1.8 and 1.4 per cent higher yields over oats pure,berseem pure. 1/3 berseem + 2/3 oat and 2/3 berseeni + 1/3 oat respectively.Berseem pure was not benefited by the application of nitrogen, while itrespond well co the application of 80 kg PÂ205 per hectare. Forageproduction from 1/2 berseem + 1/2 oat mixture was appreciably improvedby the application of 40 kg Nand 40 kg PÂ205 per hectare. Oatspure responded markedly to the application of 80 kg N/ha, while it was least responsive to phosphorus application. The practice of growing'1/2 berseem + 1/2 oat mixture with the application of nitrogen phisphosphate each at the rate of 40 kg per hectare may be adopted withadvantage.